Future perspectives on the pharmacological management of depression. (February 2013) - Yates, Sarah; Smith, Eleanor; Alhaj, Hamid A; McAllister-Williams, R Hamish
Major depressive disorder is a disabling condition that impacts on function and well-being. It is one of the leading causes of disease burden in high-income countries. Treatment of this disorder can be challenging because a significant minority of patients do not respond to initial pharmacotherapy. There has been on-going debate about the 'efficacy' of antidepressants given a large placebo response in trial data. In this nonsystematic review this is discussed and recent studies are quoted that point to more effective ways in interpreting antidepressant randomized controlled trial data. An analysis of recent studies that impact on current clinical practice is also presented, including studies of Agomelatine, antidepressant combinations and augmentation strategies. Studies that may pave the way to more effective treatments and a better understanding of the pathophysiology of this disabling condition are highlighted. These include introduction of triple reuptake inhibitors, NMDA receptor antagonists and glucocorticoid receptor antagonists.